2013
DOI: 10.2174/1874398620130508001
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Impacts of Fire Management on a Biodiversity Indicator in the Sierra Nevada and Cascades, USA: The Black-Backed Woodpecker

Abstract: Abstract:In the Sierra Nevada and southern Cascade ranges of California and Oregon, a genetically distinct population of the black-backed woodpecker has become rare due, in part, to fire suppression. This species is considered an indicator species for its primary habitat: early successional burned forests with an abundance of standing dead trees. Fuel reduction treatments such as post-fire logging, and forest thinning prior to fire (by creating insufficient snag density and enhancing fire suppression), may fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Our findings suggest that Black-backed Woodpecker occurrence in green forest is far greater than has been suggested by others (Odion and Hanson 2013), though it is still much lower than what has been reported in burned forest in this region (Seigel et al 2012), a pattern that is consistent with findings for the species elsewhere in its range (Goggans et al 1989, Trebmlay et al 2009, Rota 2013. Their distribution in green forest varies based on forest type, physiographic parameters, and habitat conditions, some of which follow patterns found in burned forest in the region.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings suggest that Black-backed Woodpecker occurrence in green forest is far greater than has been suggested by others (Odion and Hanson 2013), though it is still much lower than what has been reported in burned forest in this region (Seigel et al 2012), a pattern that is consistent with findings for the species elsewhere in its range (Goggans et al 1989, Trebmlay et al 2009, Rota 2013. Their distribution in green forest varies based on forest type, physiographic parameters, and habitat conditions, some of which follow patterns found in burned forest in the region.…”
Section: Discussionsupporting
confidence: 90%
“…Their status and occurrence patterns in Sierra Nevada green forest are unknown, although small numbers of nesting pairs have been documented outside of areas that recently burned at moderate or high severity (Raphael and White 1984). The importance of this secondary habitat may be underappreciated by researchers and managers working to conserve this rare species at the southern extent of its range (Odion and Hanson 2013). …”
Section: Introductionmentioning
confidence: 99%
“…While much of the concern about fire and thinning in dry forests of the Pacific Northwest has focused on spotted owls, it may also apply to other biota associated with dense, old forests, including species of conservation concern, such as Pacific fisher (Martes pennanti pacifica), which research indicates may benefit from mixed-severity fire (Hanson 2013), the Northern Goshawk (Accipiter gentilis), and, following fire, the Black-backed Woodpecker (Picoides arcticus), which depends upon higher-severity fire in dense, older forest (Odion and Hanson 2013). Like the spotted owl, studies have documented that this woodpecker is also negatively affected by thinning (Hutto 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To calculate rotations of severe fire in the forests of the study area, we used available fire data from a time period, 1996-2011, which includes exceptionally large, rare fire events. Our approach may be useful to managers interested in maintaining habitat for other species that rely on dense forests in fire-prone regions (Odion and Hanson 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that current rates of high-severity fire, including in frequent-fire forest types, are often substantially lower than historical rates (Odion and Hanson 2013;Baker 2014;Odion et al 2014; Hanson and Odion in press). This raises a conservation concern for the many rare and declining wildlife species positively associated with the unique, and highly biodiverse, habitat created by high-severity fire: 'complex early seral forest' -particularly given frequent post-fire logging of this habitat Hanson 2014).…”
Section: Safford Et Al (This Issue) Question Our Finding In Ijwf Inmentioning
confidence: 95%